ChemInform Abstract: A Convenient Alumination of Functionalized Aromatics by Using the Frustrated Lewis Pair Et3Al and TMPMgCl·LiCl. Issue 16 (22nd April 2014) - Unsinn, Andreas; Wunderlich, Stefan H.; Jana, Anukul; Karaghiosoff, Konstantin; Knochel, Paul
Abstract An efficient method for in situ alumination of electron‐rich aromatics is developed.